(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
There are areas of the ancient world, like the Iberian Peninsula, of whose linguistic landscape we are almost completely ignorant. In the areas lacking a contemporary native epigraphy, proper names become our only and meagre guide. But we must be conscious at all times about the frailty of the procedure and try to find additional reasons in each case to support the discussion. The Roman inscription of Uclés dedicated to a Deo Aironi is an interesting example of how the etymological study of a proper name may be confirmed by its non-linguistic context.